INFLUENCE OF TELEREHABILITATION TO IMPROVE FUNCTIONAL OUTCOMES IN INDIVIDUALS WITH PARKINSON’S DISEASES - VINCY IGNATIOUS,; RADHIKA C.M,; PRAVEEN KUMAR CHENNIMALAI RAVI,; P. PARTHIBAN, (The Bioscan, 2025)
Motor, and non-motor symptoms of Parkinson’s disease (PD), Regular practice of exercise can improve their functional capacity and overall quality of life (QOL). Interruption of physical therapy in pandemic severely affected the patient’s QOL. Tele- rehabilitation services (TR), prevents delay of care, improves, maintain, motivates, and satisfies the patient, also boosted the opportunity to apply technology-based solutions to provide health services without interruption. Aim: To find the effectiveness of Tele rehabilitation on functional outcome in clients with Parkinson’s disease. Materials and methods: An observational study was conducted on 11 individuals diagnosed with Idiopathic PD recruited from a private clinic. Unified Parkinson’s Diseases Rating Scale was used to assess the functional status of the patient. Tele rehab training is given for 4 weeks on alternate days for 30 minutes duration under the guidance of an experienced therapist. At the end of the fourth week, the subjects were re-evaluated using the UPDRS scale. Results: Significantly improved UPDRS motor component, as well as total UPDRS score, showed in individuals diagnosed with PD. Conclusions: People with PD, who can’t reach clinical setup easily, will find Telerehabilitation more affordable. It is possible to perform treatment programs for people with PD using the telerehabilitation system.